An Analysis of the Mathematics Textbook for the First Grade in Jordan in Light of the National Council of Mathematics Teachers (NCTM) Standards - Darwish , Haitham Fuad; Abed , Eman Rasmi (Dirasat: Educational Sciences, 2023)
Objectives: This study aimed to investigate the extent to which the content of the basic first-grade mathematics textbook in Jordan complies with the standards of the National Council of teachers of mathematics (NCTM). The study’s authors expect that it will help those responsible for creating mathematics curricula at all levels, and in the fundamental first grade in particular, by highlighting areas of strength and need. Method: The study sample consisted of a mathematics book for the first grade in Jordan, with its first and second parts, and two exercise books. An analysis instrument was designed; the validity and reliability of the instrument were ensured. The analysis process was carried out by monitoring the set of paragraphs, each of which includes one idea, and then calculating the number of ideas that represent one of the elements of the analysis, and calculating their repetitions and percentages in light of the sum of repetitions of the elements of the criterion. Results: The results of the study showed that the content of the first-grade mathematics textbook was the highest in data analysis and probability (0.00−79.31)% while it was the lowest in numbers and operations (0.00−18.69)%. The results also showed that the extent of the operations standards was the highest in problem-solving (0.00−76.92)% and the lowest was in communication (3.57−35.71)%. Conclusions: The study recommended the necessity of developing the book according to NCTM standards, and conducting studies to evaluate mathematics books for other classes in light of the current curricular development movement in Jordan.